Naming as cultural artifacts: a look at Malaysian famous Makciks and Pakciks / Nazima Versay Kudus - Versay Kudus, Nazima (Academy of Language Studies, 2022)
Asian culture pays great attention to mannerism especially to that of someone older. In the Malay culture, for instance, a person’s hierarchy in the family is important so that appropriate form of address can be used. One’s reference as Mak so-and-so (aunt so-and-so) or Pak so-and-so (uncle so-and-so) in extended family is based on the birth order of the person in her/his nuclear family. Take for example, a first child born to a couple will be addressed as Along or Kak Long if it is a female, or Abang Long for a male. Among her/his nieces and nephews, she/he automatically becomes Mak Long or Pak Long.